Evaluate the level of creative support of the teaching process of football game tactics - Duda, H.; Stula, A. (Journal of Kinesiology and Exercise Sciences, 2017)
Teaching tactics in team games is a difficult process, because it requires not only the optimal preparation of the player in the physical and physical sphere but above all the deliberate action in the sport. Situations that arise when playing football, usually require the choice of one of several possible decisions. Not all decisions are optimal. It is on the basis of the optimal decision that you can judge the advantages of the player and then interpret his abilities. In order to rationally solve a task in the game, the player must have the best knowledge about the effective action, and they also need to use such tactical preparation methods so that the player can consciously and creatively participate in the training process. The purpose of research Determine whether modern football clubs are using tactical training based on creative support in teaching football tactics. Material and methods of testing The empirical material was collected by anonymous polls conducted among randomly selected football players in two age categories: junior (140 CLJ players and MW leagues) and senior (160 players IV and III leagues). Research in the years 2015 - 2017 was conducted in randomly selected Polish clubs, with the largest number (about 80%) being players in the Malopolskie, Swietokrzyskie, Podkarpackie, Silesian, Opole and Lubuskie voivodships. Results and conclusions The analysis of the research results shows that football players in the clubs surveyed are less likely to benefit from the knowledge transfer, which facilitates learning tactics. The reason for this situation is not only due to the limited organizational conditions for rational training but also can have its basis in the competence of trainers. This problem is significant for young players, which can limit not only the smooth operation of the game but also hinder the process of full development of the player. 1). Tactical training dominates traditional forms of instruction that limit the player's conscious participation in the game. 2). Among the trainers there is a low level of knowledge about the use of tactics to help teach the tactics of the game. 3) . In order to make more use of the teaching aids tactics, there is a need to include this learning direction in the training of trainers and football instructors. 4). Base conditions in football clubs limit the use of modern laboratory measures in teaching tactics.